Kawista Fruit (Limonia Acidissima) Extract as an Alternative Reduction of Vomiting in Pregnancy (Study of Laboratory in Mice) - Nurul Hidayati (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Background Nausea and vomiting are common symptoms in pregnancy and occur in 50-90% of pregnant women. Although mice are unable to vomit they display a gaping reaction when their serotonin levels increase. Serotonin levels in non-pregnant mice approach the lower detection threshold (0.004pmol / islet). And it increases 200 times during pregnancy. High serotonin levels can cause nausea. Vitamine B6 is believed to be a safe and effective drug to reduce nausea and vomiting in pregnancy. Kawista fruit extract has a high vitamine B6 content. Side effects on vitamine B6 drugs are severe allergic reactions (rash; hives; difficulty breathing; tightness in the chest; swelling in the mouth, face, lips, or tongue); decreased sense of touch, temperature, or vibration; loss of balance; numbness in the legs or around the mouth; numbness or tingling in the skin. Objective The aim of the study was to prove the effect of kawista fruit extract to reduce the frequency of nausea in mice. Method This study is a quantitative study that uses an experimental design model with one-group pre-test and post-test design. The number of samples used was 20 muskulus mice which were divided into 4 groups, 5 controls, 5 POR, 5 kawista 0.5mg and 5 kawista 1.0mg. The examination was carried out for 6 days including gaping / gaping reflexes in mice. The sampling technique was random sampling with regard to inclusion criteria. Data analysis using Kruskal Wallis statistical test followed by Post Hoc. Results The results of this study showed a decrease in nausea and vomiting before and after intervention, the average number of gaping on day 4 in the kawista fruit treatment group was 1.0 mg, 6 times or 62% per day and value 0,000 (<? = 0, 05), the average number of gaping in the kawista fruit extract treatment group dose of 0.5 mg is 7 times or 66% per day and p value 0,000 and while the POR group has an average value of nausea vomiting 8 times per day or 84% and p value 0.008. Conclusions and suggestions It can be concluded that there is an effect of consumption of kawista fruit extract to reduce nausea in mice. Based on the results of these studies it is suggested to be able to apply the use of kawista fruit especially in maternal health services.Background Nausea and vomiting are common symptoms in pregnancy and occur in 50-90% of pregnant women. Although mice are unable to vomit they display a gaping reaction when their serotonin levels increase. Serotonin levels in non-pregnant mice approach the lower detection threshold (0.004pmol / islet). And it increases 200 times during pregnancy. High serotonin levels can cause nausea. Vitamine B6 is believed to be a safe and effective drug to reduce nausea and vomiting in pregnancy. Kawista fruit extract has a high vitamine B6 content. Side effects on vitamine B6 drugs are severe allergic reactions (rash; hives; difficulty breathing; tightness in the chest; swelling in the mouth, face, lips, or tongue); decreased sense of touch, temperature, or vibration; loss of balance; numbness in the legs or around the mouth; numbness or tingling in the skin. Objective The aim of the study was to prove the effect of kawista fruit extract to reduce the frequency of nausea in mice. Method This study is a quantitative study that uses an experimental design model with one-group pre-test and post-test design. The number of samples used was 20 muskulus mice which were divided into 4 groups, 5 controls, 5 POR, 5 kawista 0.5mg and 5 kawista 1.0mg. The examination was carried out for 6 days including gaping / gaping reflexes in mice. The sampling technique was random sampling with regard to inclusion criteria. Data analysis using Kruskal Wallis statistical test followed by Post Hoc. Results The results of this study showed a decrease in nausea and vomiting before and after intervention, the average number of gaping on day 4 in the kawista fruit treatment group was 1.0 mg, 6 times or 62% per day and value 0,000 (<? = 0, 05), the average number of gaping in the kawista fruit extract treatment group dose of 0.5 mg is 7 times or 66% per day and p value 0,000 and while the POR group has an average value of nausea vomiting 8 times per day or 84% and p value 0.008. Conclusions and suggestions It can be concluded that there is an effect of consumption of kawista fruit extract to reduce nausea in mice. Based on the results of these studies it is suggested to be able to apply the use of kawista fruit especially in maternal health services.